(untitled) (Indian Journal of Animal Production and Management, 2024)
Sexual behaviour in cattle and buffaloes is influenced by various factors such as seasonality, reproductive physiology, and social dynamics. This behaviour includes reaction time, courtship, sexual aggressiveness, penile erection, and ejaculatory thrust. Testosterone, kisspeptin and pheromones significantly influence sexual behaviour affecting reaction time, sexual aggressiveness, and penile erection. In addition, environmental conditions can impact the physiological aspects of bulls, including hormone secretion, energy metabolism and fatty acid oxidation. These factors subsequently influence the sexual behaviour and semen quality of bulls, with temperature, humidity and seasonal variations being significant contributors. Stressors related to sexual behaviour, such as the transportation of animals for mating or confrontations between bulls, can have detrimental effects on semen quality. Furthermore, adequate peri-conception and post-natal nutrition received by the calf also affects its postnatal health, gonadal development, gamete quality and the hormonal status ultimately affecting its sexual expression and behaviour. Lastly, bulls that sustain physical injuries or infections from sexual encounters may exhibit a decline in sexual behaviour, impacting their semen quality. This paper presents a literature review on sexual behaviour of bulls and its consequences for welfare and quality semen production with special focus on in Indian native cattle and buffaloes.